Application of probiotic therapy in nonalcoholic fatty liver disease: mediating mechanism and future perspective - Luo, Xing-Yu; Huang, Wei-Bin; Lu, Chuang-Hui; Gu, Wu; Feng, Zi-Xuan; Shen, Sui; Chen, Ming-Zheng; Zheng, Shu-Sen; Yang, Zhe (Frontiers in Cellular and Infection Microbiology, 2025)
Nonalcoholic fatty liver disease (NAFLD) has a global prevalence of 20%-33%, and has become the main cause of chronic liver disease. Apart from lifestyle modification therapy, there is currently no definitive pharmacological treatment, thus there is an urgent need to find effective intervention strategies to treat NAFLD. With the discovery of the important role of gut microbes in the pathogenesis of NAFLD, research on the prevention and treatment of non-alcoholic fatty liver disease by probiotics is increasing. At present, many studies have confirmed the role of probiotic regulation in the treatment of NAFLD, which can reduce the level of transaminase and liver fibrosis in patients and protect the liver. The clinical application of probiotics includes single species such as Lactobacillus and Bifidobacteria, as well as synbiotics with different compositions. This article reviews the therapeutic effects of probiotics on NAFLD and the mechanisms by which probiotics directly or indirectly affect the disease. Further research is needed to fully understand the specific underlying mechanisms between probiotics, gut microbes, and NAFLD, and more large-scale clinical trials are needed to evaluate probiotics for the treatment of NAFLD.